Histology of Interstitial Lung Disease in Common Variable Immune Deficiency - Dhalla, Fatima; Lochlainn, Dylan J. Mac; Chapel, Helen; Patel, Smita Y. (Frontiers in Immunology, 2020)
Interstitial lung disease (ILD) is an important non-infectious complication in several primary immune deficiencies. In common variable immune deficiency (CVID) it is associated with complex clinical phenotypes and adverse outcomes. The histology of ILD in CVID is heterogeneous and mixed patterns are frequently observed within a single biopsy, including non-necrotising granulomatous inflammation, lymphoid interstitial pneumonitis, lymphoid hyperplasia, follicular bronchiolitis, organizing pneumonia, and interstitial fibrosis; ILD has to be differentiated from lymphoma. The term granulomatous-lymphocytic interstitial lung disease (GLILD), coined to describe the histopathological findings within the lungs of patients with CVID with or without multisystem granulomata, is somewhat controversial as pulmonary granulomata are not always present on histology and the nature of infiltrating lymphocytes is variable. In this mini review we summarise the literature on the histology of CVID-related ILD and discuss some of the factors that may contribute to the inter- and intra- patient variability in the histological patterns reported. Finally, we highlight areas for future development. In particular, there is a need for standardisation of histological assessments and reporting, together with a better understanding of the immunopathogenesis of CVID-related ILD to resolve the apparent heterogeneity of ILD in this setting and guide the selection of rational targeted therapies in different patients.